BIOAKTIVITAS EKSTRAK LIMBAH BUAH BAKAU (Rhizophora mucronata Lamk) TERHADAP RAYAP TANAH Coptotermes vurvignathus Holmgren - Fitriyani, Rika Ayu; Diba, Farah; Yusro, Fathul (JURNAL HUTAN LESTARI, 2019)
The mangrove heap of Rhizophora mucronata Lamk as a result of planting activities managed by a community group called Surya Perdana Mandiri in Singkawang City, Setapuk Besar Village was not utilized, due to lack of information and knowledge of the community about the benefits of this type. This study aims to analyze phytochemical compounds from fruit mangrove extracts of R. mucronata, then analyzing the bioactivity of extracts against subterranean termites Coptotermes curvignathus and determine the optimum concentration of R. mucronata mangrove fruit extracts wich inhibited the activity of subterranean termites C. curvignathus. Fruit of R. mucronata was extraction with aquades for three hours with a temperature of 50Â°C. Then the extract was made into concentration 2%, 4%, 6%, 8%, and 10%. The filter paper was dip in extract solution then put into medium as a food source for termites for 21 days. The mortality of termites and weight loss of filter paper was analyzed to evaluate the inhibition assay.This study uses a completely randomized design method and statistical calculations using SPSS 22. Termite mortality at a concentration of 0% (control) is significantly different from all concentrations. However, when compared between concentrations (2, 4, 6, 8, and 10%) the difference was not significant, meaning that mortality between concentrations did not have a significant effect. Weight loss of filter paper at a concentration of 0% (control) was significantly different from a concentration of 10%. The results showed that the concentration of 10% of R. mucronata mangrove extract was an optimum concentration to inhibited the subterranean termites Coptotermes curvignathus with a mortality value of 92% and a weight loss value of 26.91%.Keyword : antitermites, bioactivity, Coptotermes curvignathus Holmgren, fruit waste, Rhizophora mucronata Lamk